Computerisation of a police department in a state in Western India - Verma, Sanjay (London : Indian Institute of Management, Ahmedabad, 2015)
Mr. Ajay Vasav, Inspector General of Police of ASWI (A state in Western India) shared his apprehensions about the computerisation process in the state. This initiative was being taken when the Government of India had envisaged a centralised crime and criminal tracking system to harness the power of information technology.
Originally published in Verma, S. (2015). Computerisation of a police department in ASWI. CISG0132. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Law enforcement -- Effect of automation on -- India; Computers and civilization